The pericytic phenotype of adipose tissue-derived stromal cells is promoted by NOTCH2 - Terlizzi, Vincenzo; Kolibabka, Matthias; Hammes, Hans-Peter (Stem cells, 2018)
Long-term diabetes leads to macrovascular and microvascular complication. In diabetic retinopathy (DR), persistent hyperglycemia causes permanent loss of retinal pericytes and aberrant proliferation of microvascular endothelial cells (ECs). Adipose tissue-derived stromal cells (ASCs) may serve to functionally replace retinal pericytes and normalize retinal microvasculature during disease progression. We hypothesized that Notch signaling in ASC underlies regulation and stabilization of dysfunctional retinal microvascular networks such as in DR. ASC prominently and constitutively expressed NOTCH2. Genetic knockdown of NOTCH2 in ASC (SH-NOTCH2) disturbed the formation of vascular networks of human umbilical cord vein endothelial cells both on monolayers of ASC and in organotypical three-dimensional cocultures with ASC. On ASC SH-NOTCH2, cell surface platelet-derived growth factor receptor beta was downregulated which disrupted their migration toward the chemoattractant platelet-derived growth factor beta subunits (PDGF-BB) as well as to conditioned media from EC and bovine retinal EC. This chemoattractant is secreted by pro-angiogenic EC in newly formed microvascular networks to attract pericytes. Intravitreal injected ASC SH-NOTCH2 in oxygen-induced retinopathy mouse eyes did not engraft in the preexisting retinal microvasculature. However, the in vivo pro-angiogenic capacity of ASC SH-NOTCH2 did not differ from controls. In this respect, multifocal electroretinography displayed similar b-wave amplitudes in the avascular zones when either wild type ASC or SH-NOTCH2 ASC were injected. In conclusion, our results indicate that NOTCH2 is essential to support in vitro vasculogenesis via juxtacrine interactions. In contrast, ongoing in vivo angiogenesis is influenced by paracrine signaling of ASC, irrespective of Notch signaling. Stem Cells 2018;36:240-251